Investigating critical thinking skills in Arabic textbooks exercises of junior high schools based on Lipman's Theory - Fatemeh Irandoost; Maryam Jalaei; Abbas Zare-ee Tajareh (دراسات في اللغة العربيّة وآدابها)
In efficient educational systems, it is believed that in today's changing world, the science lifetime is so short and the issues must be considered critically; therefore, it has been attempted to improve and flourish this kind of thinking in different educational backgrounds and levels. Accordingly, the purpose of the present study is to analyze the Arabic textbooks exercises of junior high schools regarding the attention paid on critical thinking skills discussed in Lipman's Theory. The methodology applied in this research is descriptive as well as content analysis methodology and Shannon entropy weighting method has been used in order to determine the importance coefficient of the studied components. Statistical sample and population coincide on each other including all of the exercises in Arabic textbooks of junior high schools in academic year of 1401-1402 Hijri/ 2022-2023 A.D. The books are in three volumes. In order to obtain the purposes of the research, a list of Lipman's critical thinking skills has been utilized as research tool including nine components as follows; Being collective, questioning, assessing evidence and statements, argumentation, interpretation, analysis, logic, being explicit, and judge. Based on the research data in all three educational levels, the three components of interpreting, analyzing and assessing evidence and statements have the highest frequency and the three components of being explicit, judging and reasoning have the lowest frequency; Generally The findings of the research illustrate that, Lipman's critical thinking skills have not been paid balanced and equal attention. These results also indicate that incongruity in using different skills have been increased in parallel with studying in higher grades. So, in this regard, the studied educational content requires to be reviewed and corrected.